COMMENTARY AS A JOURNALISTIC GENRE OF DIGITAL MEDIA IN THE AGE OF INFORMATION OVERLOAD - Deleva; Vitković, Biljana (Political Review, 2025)
The modern moment is marked by absurdity: there is more and more information, but never less information content. This is best illustrated by the quality of content in the media since the unstoppable technical and technological waves and the dominance of social networks began. The content is produced on a mass-produced basis, which calls into question its authenticity and quality. The main characteristic of the media sphere is, therefore, hyperproduction, and society is overloaded with information. This paper examines the most important characteristics and quality of author comments in the digital information media „Politika“, „Danas“, and „Telegraf“. The analysis included comments with the aim of determining the extent to which this analytical journalistic form is represented as an original authorial text and to what extent it is used as inspiration for writing original content. The paper is based on a theoretical framework that encompasses the concepts of media hyperproduction, algorithmic selection of media content, and analytical journalism as a response to the crisis of originality. The main determinants of the comments were determined using the content analysis method. The content of the articles was analyzed through the following categories: topic, topicality, value judgment and significance, tone of the comment, graphic presentation, sources, style, and authorship of the comment. The research results show variability in the quality and representation of comments, from well-argued to superficial, without in-depth analysis. This phenomenon indicates the challenges in maintaining quality and creating original content in conditions of hyperproduction. Insufficient staffing and financial support are obstacles to the development of analytical journalism, while the role of education and algorithms further complicates the status of comments as a genre. This indicates the need for a systemic and strategic approach in digital media to overcome the above problems. The lack of original content deepens existing and opens up new media issues, and such work can be a starting point for a systemic approach and larger-scale research.